Little Words, Big Impact: Determiners Begin to Bootstrap Reference by 12 Months. Issue 3 (3rd July 2017) - Kedar, Yarden; Casasola, Marianella; Lust, Barbara; Parmet, Yisrael
ABSTRACT: We tested 12- and 18-month-old English-learning infants on a preferential-looking task which contrasted grammatically correct sentences using the determiner "the" vs. three ungrammatical conditions in which "the" was substituted by another English function word, a nonsense word, or omitted. Our design involved strict controls on phonetic composition of function words and co-articulation effects in the stimuli tested, which were absent in previous studies. The results show an overall significant effect of Function Word (FW), with no significant interaction effects between the two age groups. Overall, infants oriented faster to a target image and had more correct first looks at target following grammatical sentences. Tests within age groups show a significant effect of FW in 18-month-olds for both latency and correct first look, documenting a linguistic sensitivity, which persists over our new acoustic variables. In the 12-month-olds there was a significant effect of FW on first look, although no significant effect of FW for latency appeared. However, pairwise comparisons showed a significant difference between grammatical and ungrammatical FWs in latency even at this age. These findings suggest that some prototypical form of sensitivity to determiners in sentence processing and its use in computing noun reference exists already during early developmental stages surrounding the child's first words. We speculate on potential explanations for developmental changes between 12 and 18 months.